Trachoma prevalence and associated risk factors in the gambia and Tanzania: baseline results of a cluster randomised controlled trial. - Emma M Harding-Esch; Tansy Edwards; Harran Mkocha; Beatriz Munoz; Martin J Holland; Sarah E Burr; Ansumana Sillah; Charlotte A Gaydos; Dianne Stare; David C W Mabey; Robin L Bailey; Sheila K West; et al. (Public Library of Science (PLoS), 2010)
Blinding trachoma, caused by ocular infection with Chlamydia trachomatis, is targeted for global elimination by 2020. Knowledge of risk factors can help target control interventions.As part of a cluster randomised controlled trial, we assessed the baseline prevalence of, and risk factors for, active trachoma and ocular C. trachomatis infection in randomly selected children aged 0-5 years from 48 Gambian and 36 Tanzanian communities. Both children's eyes were examined according to the World Health Organization (WHO) simplified grading system, and an ocular swab was taken from each child's right eye and processed by Amplicor polymerase chain reaction to test for the presence of C. trachomatis DNA. Prevalence of active trachoma was 6.7% (335/5033) in The Gambia and 32.3% (1008/3122) in Tanzania. The countries' corresponding Amplicor positive prevalences were 0.8% and 21.9%. After adjustment, risk factors for follicular trachoma (TF) in both countries were ocular or nasal discharge, a low level of household head education, and being aged ≥ 1 year. Additional risk factors in Tanzania were flies on the child's face, being Amplicor positive, and crowding (the number of children per household). The risk factors for being Amplicor positive in Tanzania were similar to those for TF, with the exclusion of flies and crowding. In The Gambia, only ocular discharge was associated with being Amplicor positive.These results indicate that although the prevalence of active trachoma and Amplicor positives were very different between the two countries, the risk factors for active trachoma were similar but those for being Amplicor positive were different. The lack of an association between being Amplicor positive and TF in The Gambia highlights the poor correlation between the presence of trachoma clinical signs and evidence of C. trachomatis infection in this setting. Only ocular discharge was associated with evidence of C. trachomatis DNA in The Gambia, suggesting that at this low endemicity, this may be the most important risk factor.ClinicalTrials.gov NCT00792922.